Application of PS-INSAR Technique on Health Diagnosis of the Deformable Body on Front Slope beside Mountain Tunnel Portal. (29th November 2020) - Jia, Jiaxin
Abstract : When tunnel construction develops to surrounding mountainous areas, tunnel portal presents the topographic characteristics of "high, steep, and slant" and geological characteristics of kinds of hugely thick colluvial or residual slope, and the health condition of the deformable body on front slope beside tunnel portal has a great influence on tunnel construction and operation. Tunnel portal has suffered from many disasters, and it is urgent to study and solve the engineering problem on how to diagnose the health condition of front slope beside tunnel portal quickly and accurately. Based on the tunnel of Jianquan village, this paper uses PS-INSAR technique for the first time to analyze and diagnose the health condition of the deformable body on front slope beside mountain tunnel portal at the construction stage and operation stage, so as to provide early warnings to unstable deformable body at tunnel portal and provide strong bases for the treatment of unstable deformable body. Therefore, PS-INSAR technique promotes the health monitoring method for deformable body on front slope beside mountain tunnel portal to a higher level.